Judicial Interpretation of Waqf Land Validity in Indonesia: A Comparative Analysis of Positive Law and Islamic Law through Case Decision No. 453/Pdt.G/2020/PA.Kdi - Paramitha, Attahiraa Prajna; Huda, Miftahul (Berasan: Journal of Islamic Civil Law, 2025)
Waqf has long functioned as both a religious act of worship and a social instrument that sustains community development in Muslim societies. Nevertheless, disputes frequently arise concerning the legal validity of waqf land, particularly when the procedures deviate from statutory regulations. This study examines the judicial reasoning behind Decision No. 453/Pdt.G/2020/PA.Kdi of the Religious Court of Kendari, which involved a conflict between two nazhirs claiming authority over the same waqf land. Employing normative legal research with a case approach and drawing on secondary legal materials, the study analyzes the intersection between Indonesian positive law—represented by Law No. 41/2004 on Waqf, Government Regulation No. 42/2006, and the Compilation of Islamic Law—and Islamic legal principles concerning waqf validity. The findings reveal that the court invalidated the first waqf due to the absence of an authentic deed, thereby prioritizing procedural formalities under statutory law. However, from the standpoint of Islamic law, the waqf remained valid as it fulfilled the essential pillars of waqf, namely waqif, mauquf, mauquf ‘alaih, and sighat. This divergence underscores the tension between formal legal certainty in positive law and the substantive validity emphasized in Islamic jurisprudence. The article contributes to scholarly debates on legal pluralism in Indonesia, offering insights into how judicial decisions navigate between state law and Islamic legal doctrines in resolving waqf disputes.